Enhancing the electrochemical properties of a Nickel-CobaltManganese ternary hydroxide electrode material using graphene foam for supercapacitors applications - Manyala, Ncholu I. (University of Pretoria, 2021)
Dissertation (MSc (Chemical Technology))--University of Pretoria, 2020.